Leaf mass area determines water use efficiency through its influence on carbon gain in rice mutants. Issue 2 (12th March 2020) - Reddy, Sowmya Handenahally; Singhal, Rajesh Kumar; DaCosta, Maria Vera Jesus; Kambalimath, Sumanth Kumar; Rajanna, Mavinahalli P; Muthurajan, Raveendran; Sevanthi, Amitha Mithra; Mohapatra, Trilochan; Sarla, Neelamraju; Chinnusamy, Viswanathan; S, Gopala Krishnan; Singh, Ashok Kumar; et al.
Abstract : Saving water and enhancing rice productivity are consensually the most important research goals globally. While increasing canopy cover would enhance growth rates by higher photosynthetic carbon gain, an accompanied increase in transpiration would have a negative impact on saving water as well as for sustainability under water‐limited conditions. Increased water use efficiency (WUE) by virtue of higher carbon assimilatory capacity can significantly circumvent this trade‐off. Here, we report leaf mass area (LMA) has an important canopy architecture trait which when combined with superior carboxylation efficiency (CE) would achieve higher water productivity in rice. A set of 130 ethyl methanesulfonate induced mutants of an upland cultivar Nagina‐22 (N22), was screened for leaf morphological traits leading to the identification of mutants differing in LMA. The wild‐type, N22, along with a selected low‐LMA (380–4‐3) and two high‐LMA mutants (392–9‐1 and 457–1‐3), all with comparable total leaf area, were raised under well‐watered (100% Field Capacity (FC)) and water‐limited (60% FC) conditions. Low Δ 13 C and a higher RuBisCO content in high‐LMA mutants indicated higher carboxylation efficiency, leading to increased carbon gain. Single parent backcross populations developed by crossing high and the low‐LMA mutants with N22, separately, were screened for LMA, Δ 13 C and growth traits. Comparison of dry matter accumulation per unit leaf area among the progenies differing in LMA and Δ 13 C reiterated the association of LMA with CE. Results illustrated that high‐LMA when combined with higher CE (low Δ 13 C) lead to increased WUE and growth rates.